2015
DOI: 10.1021/acs.biochem.5b00091
|View full text |Cite
|
Sign up to set email alerts
|

An Independently Folding RNA G-Quadruplex Domain Directly Recruits the 40S Ribosomal Subunit

Abstract: In this study, we report that a 17-nucleotide independently folding RNA G-quadruplex (GQ) domain within the 294-nucleotide human VEGF IRES A interacts with the 40S ribosomal subunit. Footprinting and structure mapping analyses indicate that the RNA GQ forms independently and interacts directly with the 40S ribosomal subunit in the absence of other protein factors. Moreover, a filter binding assay in conjunction with enzymatic footprinting clearly established that the GQ-forming domain singularly dictates the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 37 publications
0
37
0
Order By: Relevance
“…The G4 formation in the vascular endothelial growth factor ( VEGF-alpha ) proximal promoter region was previously reported (66,67), and subsequent studies revealed the 5′ RNA G-quadruplex structure that is also essential for IRES-mediated translation initiation and ribosome recruitment to its mRNA (68,69). We observed notable consistency between QmRLFS, DRIP-seq and DRIPc-seq data in the VEGF-alpha proximal promoter region of NT2 and K-562 cells (Figure 3C).…”
Section: Resultsmentioning
confidence: 88%
“…The G4 formation in the vascular endothelial growth factor ( VEGF-alpha ) proximal promoter region was previously reported (66,67), and subsequent studies revealed the 5′ RNA G-quadruplex structure that is also essential for IRES-mediated translation initiation and ribosome recruitment to its mRNA (68,69). We observed notable consistency between QmRLFS, DRIP-seq and DRIPc-seq data in the VEGF-alpha proximal promoter region of NT2 and K-562 cells (Figure 3C).…”
Section: Resultsmentioning
confidence: 88%
“…Sequences in 5′ UTRs capable of forming RG4s are a functionally important part of the VEGFA IRES 129,130 and a structural feature of the FGF2 IRES 131 , contributing to IRES-mediated translation of both mRNAs. Although the exact functional role of the FGF2 RG4 has not yet been studied, the VEGFA RG4 within the IRES, which in vitro folds independently of the IRES, is required to directly recruit the 40S ribosomal subunit, as shown by in vitro footprinting and structure mapping 132 , although this remains to be confirmed in vivo .…”
Section: Ires Structures and Functionmentioning
confidence: 99%
“…RNA (GGGGCC) n repeats are capable of forming G4s 94; 114; 161; 162 and bioactive small molecules targeting these repeats significantly inhibit RAN translation and the production of dipeptide repeat proteins 162 . As different RNA G4s are able to interact with ribosomal proteins 93 and/or bind the 40S ribosomal subunit 163 , we propose that C9ORF72 hexameric RNA G4 repeats may directly recruit translationally-competent 48S-like pre-initiation complexes to initiate RAN translation generating di-peptides. We are currently testing this hypothesis (Figure 7B).…”
Section: Proposed Functions Of Rna G-quadruplexesmentioning
confidence: 99%